Improving Students' Reading Comprehension through Read, Encode, Annotate and Ponder (REAP) Technique - Andi Hapsa Mulinda; Saepudin (Inspiring: English Education Journal, 2021)
Reading is very important comprehension in learning English. There are many techniques that can be used by teachers to improve the students’ reading comprehension, but there are many obstacles they have in using learning technique. The problem arises when many students got bored in reading. They have limited vocabularies which make them have low motivation to read the text. To solve this problem, the researcher used read, Encode, Annotate, and Ponder (REAP) technique as a technique to improve the students’ reading comprehension. This technique was chosen to find out the main idea in the story reading assignment and also make students were active in the class. The purpose in this study was to find the students’ reading comprehension before and after the learning process by using Read, Encode, Annotate, and Ponder (REAP) technique. The design in this research was pre-experimental with pre-test and post-test design. The population of this research was the eighth grade students of MTs Guppi Kaluppang Kab. Enrekang. There are 41 students and they were divided into two classes. The sample was taken by using random sampling technique. The researcher took the class VIII A which was consisting of 20 students as the sample in this researcher. The result in this research was indicated that there was improvement of the students’ reading comprehension. It was indicated by the students’ mean score post-test (88,45) was greater than pre-test (51.00). Even, for the level significant (p) 5% and df = 19, and the value of table is 1.729, while the value of t-test is 19.60. It means that the t-test value was greater than t-table (19.60 ≥ 1.729). Thus, it can be conclude that the students’ reading comprehension is significant better after getting the treatment. The students’ response through the questionnaire also had calculated on the finding, the result showed all the students’ answered positive and most of them got 50%-74.99%. The main score of the students was 71.45 from 20 students which was categorized responsive.